Creative Insubordination in the Continuing Education of Teachers Who Teach Mathematics in the Early Years: A Study with Teachers Participating in a Research Group - dos Santos, Maria José Costa; Sousa Neta, Felismina de; Scipião, Lara Ronise de Negreiros Pinto (Lia Center of Research and Education, 2026)
Continuing teacher education represents a significant moment of rupture, allowing for reflection on traditional pedagogical practices. Therefore, we question: how does Creative Insubordination (CI) influence the change in posture of teachers who teach mathematics in the early years of elementary school during continuing education? The objective of this study is to analyze the influence of Creative Insubordination on the change in posture of teachers who teach mathematics in the early years of elementary school during continuing education. It is a qualitative study, aiming to discuss CI with teachers who are members of the Research and Study Group Weaving Cognitive Learning Networks (G-TERCOA/CPNq/UFC). For data collection, we sent a questionnaire with open-ended questions via Google Forms. The questionnaire data were analyzed according to the Fedathi Sequence as a Methodology for Data Analysis (SFMAD), based on four sub-phases: curation, detail, presentation, and interpretation. The research demonstrates that the continuing education of mathematics teachers faces the challenge of fostering innovative-collaborative pedagogical practices, highlighting IC (Innovative Communication) as a relevant concept for promoting teacher autonomy and critical reflection. We conclude that continuing education makes it possible to overcome traditional pedagogical practices, such as institutional resistance and pressure for standardized results. Thus, it is necessary to be creatively insubordinate to implement significant changes in the educational context. The study suggests that continuing teacher education could more systematically incorporate the principles of Creative Insubordination, promoting critical, creative, and innovative-collaborative pedagogical practices in order to strengthen the emancipatory role of teaching.